Motion sensors in multiple sclerosis: Narrative review and update of applications. (2nd November 2017) - Sasaki, Jeffer Eidi; Sandroff, Brian; Bamman, Marcas; Motl, Robert W
ABSTRACT: Introduction : The use of motion sensors for measuring physical activity in multiple sclerosis (MS) has evolved with increasing research particularly during the past decade. Areas covered : This manuscript reviews the literature regarding the application of motion sensors for measuring physical activity in MS. We first describe 'what is known' about their use in MS by examining the evidence generated between 1997 and 2012, including the psychometric properties of motion sensors in MS and the development of MS-specific accelerometer cut-points. We then evaluate 'what is new' based on research conducted between 2013 and 2017. This includes newer research on psychometric properties of motion sensors in MS, development of new MS-specific accelerometer and step-rate cut-points, sedentary behavior assessment, and research on fitness trackers and multisensors in MS. The final part presents a picture of 'what is next' for the applications of motion sensors in MS, especially pertaining new opportunities for testing and using fitness trackers in MS, and tracking disease and disability progression based on motion sensor output. Expert commentary : The use of motion sensors in MS has grown substantially over the years; however, a lot more can be done to explore the full potential and utility of these devices in MS.